Natural disasters and their effects in Jerusalem in the Mamluk era (648 – 923 AH 1250 – 1516 AD) - Naji, Hmydan Mahmoud (Journal of Humanities & Social Sciences, 2023)
During the Mamluk era, the city of Jerusalem was subjected to disasters, epidemics and plagues that greatly affected the city and the human losses resulting from it and its impact on the plant and animal wealth. The economic effects also included the agricultural pests that the city of Jerusalem was exposed to, especially the locusts that attacked and harvested the crops. The city of Jerusalem has been subjected to many climatic disasters, including torrential rains and torrential rains that fell on it and caused damage to buildings and residential facilities. Jerusalem has been subjected to many earthquakes, especially in The Circassian era resulted in the demolition of architectural facilities and the migration of some residents, as well as damage to schools, the Church of the Holy Sepulcher and public places The Mamluk sultans and princes took care of the holy places and their keenness to provide them with their needs from the water facilities that they built near the Dome of the Rock and the Al-Aqsa Mosque due to the increasing natural needs of the city’s residents and visitors.